2006
DOI: 10.1128/aac.00711-05
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Pharmacokinetic and Pharmacodynamic Indices of Marbofloxacin in Turkeys

Abstract: Fluoroquinolones are extensively used in the treatment of systemic bacterial infections in poultry, including systemic Escherichia coli bacillosis, which is a common disease in turkey flocks. Marbofloxacin has been licensed for use in various mammalian species, but not as yet for turkeys, although its kinetic properties distinguish it from other fluoroquinolones. For example, the longer half-life of marbofloxacin in many animal species has been appreciated in veterinary practice. It is generally accepted that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
41
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 48 publications
16
41
1
1
Order By: Relevance
“…This finding was previously reported for moxifloxacin in rabbits, 8 broiler chickens, 10 and ducks 11 and is in agreement with results of other studies of fluoroquinolones in broiler chickens, 17 turkeys, 24 and rabbits. 25 After intravenous administration, moxifloxacin in quail was rapidly distributed with half-lives of distribution of 0.3 hours, similar to results of moxifloxacin in broiler chicks at 0.26 hours 10 and 11 Moxifloxacin is slowly eliminated with an elimination half life of 2.18 hours, which is lower than that reported for danofloxacin in broiler chickens, turkeys, rabbits, and quail of 6.73, 8.64, 4.88, and 2.52 hours, respectively.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding was previously reported for moxifloxacin in rabbits, 8 broiler chickens, 10 and ducks 11 and is in agreement with results of other studies of fluoroquinolones in broiler chickens, 17 turkeys, 24 and rabbits. 25 After intravenous administration, moxifloxacin in quail was rapidly distributed with half-lives of distribution of 0.3 hours, similar to results of moxifloxacin in broiler chicks at 0.26 hours 10 and 11 Moxifloxacin is slowly eliminated with an elimination half life of 2.18 hours, which is lower than that reported for danofloxacin in broiler chickens, turkeys, rabbits, and quail of 6.73, 8.64, 4.88, and 2.52 hours, respectively.…”
Section: Discussionsupporting
confidence: 95%
“…The absorption process was rapid with T max ¼ 1.40 hours for intramuscular and T max ¼ 1.87 hours for oral administration, with k ab ¼ 1.12 and 0.76 h À1 and absorption half-life of 0.62 and 0.91 hours, for intramuscular and oral administration, respectively. These values of bioavailability are consistent with those reported for moxifloxacin in rabbits, broilers, and ducks 8,10,11 ; are in agreement with those reported for danofloxacin in broilers 17 and marbofloxacin in turkeys 24 ; and are higher than that reported for pefloxacin in ducks. 29 Effective use of concentration-dependent fluoroquinolones such as moxifloxacin while preventing selection for resistance has been associated with reaching C max 8-10 times the MIC for the pathogenic organism, rather than maintaining a concentration above MIC (time .…”
Section: Discussionsupporting
confidence: 93%
“…These values were similar to marbofloxacin (1.05±0.15 μg/ml) in broiler chickens (Anadon et al, 2002). Conversely, the reported maximum serum concentration in present study was lower than those recorded in quails 3.59±0.24 µg/ml (Aboubakr and Abdelazem, 2015) On the other hand, the acquired result of maximum serum concentration was higher than in turkey 0.80±0.32 µg/ml (Haritova et al, 2006 Goudah and Hasabelnaby, (2010). These distinctions are moderately basic and are as often as possible identified with between species variety, test techniques utilized, measure of time between blood inspecting and/or the wellbeing status and age of the creature (Haddad et al, 1985).…”
Section: Discussioncontrasting
confidence: 36%
“…This covers MIC 90 value of 0.125-0.20 g/mL against most common E. coli and other gram-negative bacterial infections except P. aeurgenosa in chickens and other birds (Spreng et al, 1995;Haritova et al, 2006 (Anadon et al, 2002). Findings of present study, indicated that the drug was rapidly distributed in the body fluids and then relatively slowly eliminated from the body in broiler chickens after single and repeated i.v.…”
Section: Resultsmentioning
confidence: 57%